UPAYA MENGEMBANGKAN POTENSI WISATA ARAK – ARAK BONDOWOSO DENGAN STRATEGI SARANA DAN PRASARANA - Hakim, Muhammad Lukman; Subairi, Afton (Jurnal Pengabdian Masyarakat dan Lingkungan, 2023)
Bondowoso Regency is one of the areas in the Besuki area. What makes it different from other regions is that Bondowoso Regency does not have a sea area, while other areas have sea areas such as Situbondo, Banyuwangi. From this condition, Bondowoso is different from other regions which do not have coastal and marine areas. Bondowoso district and local government, especially DISPARBUDPORA, focus their tourism development programs on land. The Bondowoso region has a cool area with its beauty that is still maintained so that many tourists are interested in visiting Bondowoso tourism both from domestic and foreign countries. So the Bondowoso government carried out a potential and attractiveness development program through the Bondowoso Regent's decision by giving the task to DISPARBUDPORA to make the Bondowoso region a leading tourist destination and also to improve the community's economy through the tourism sector.